An Action Research Project using the Dialogic Story Reading Approach with Children with Autism Spectrum Disorder. - Lundy, Kathryn (STER, 2020)
Research has shown that dialogic storytelling is an effective literacy intervention for children who are typically developing, and also for children with ASD (Whalon et al., 2013). This research investigated how dialogic storytelling could be used to help teachers in mainstream classes ensure that children with ASD are reaching their full potential.
Journal article.
Keywords: Research Subject Categories::SOCIAL SCIENCES; Dialogic Story-Reading; Language Development; Joint Attention; ASD